2017
DOI: 10.2166/wh.2017.162
|View full text |Cite
|
Sign up to set email alerts
|

Exploring links between water quality and E. coli O157:H7 survival potential in well waters from a rural area of southern Changchun City, China

Abstract: Waterborne infectious disease outbreak associated with well water contamination is a worldwide public health issue, especially for rural areas in developing countries. In the current study, we characterized 20 well water samples collected from a rural area of southern Changchun city, China, and investigated the survival potential of Escherichia coli O157:H7 in those water samples. The results showed that nitrate and ammonia concentrations in some well water samples exceed the corresponding China drinking water… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0
6

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 27 publications
1
3
0
6
Order By: Relevance
“…In the current study, it was found that the first log reduction time ( δ ) was significantly ( p < 0.05) correlated with ttd s. This is well in line with our previous report showing that δ was positively related with ttd of E. coli O157:H7 in well waters, as well as in agricultural soils [ 15 , 41 ]. Since δ is easier to be obtained, it could be an alternative indicator of the E. coli strains that survived in soils.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In the current study, it was found that the first log reduction time ( δ ) was significantly ( p < 0.05) correlated with ttd s. This is well in line with our previous report showing that δ was positively related with ttd of E. coli O157:H7 in well waters, as well as in agricultural soils [ 15 , 41 ]. Since δ is easier to be obtained, it could be an alternative indicator of the E. coli strains that survived in soils.…”
Section: Discussionsupporting
confidence: 92%
“…A total of 15 wells were sampled, among them 2 were covered open wells, and the rest were tube wells. For open well sampling, grab sampling technique was used; for tube well sampling, water was sampled only after the existing water in the tube was completely replaced by a large volume of fresh water [ 15 ]. All samples were collected in the morning, when maximum water usage was reached for the local community [ 15 ].…”
Section: Methodsmentioning
confidence: 99%
“…The stock EcO157 EDL931 (ATCC 35150) from−80 • C freezer was inoculated onto a fresh LB (Luria-Bertani) agar plate and incubated at 37 • C for 14-16 h [39]. A single colonywas picked up and inoculated on a solid medium containing two antibiotics (nalidixic acid 20 mg/L and rifampicin 100 mg/L) at 37 • C for 14-16 h. A single colony was selected to grow to a larger volume in LB medium; then, the cells were washed twice using 0.9% NaCl solution and resuspended in deionized water to reach OD 600nm = 1.0 for inoculation into the soilsamples.EcO157 cells were added into soils to a final density of about 0.5 × 10 7 CFU per gram soil (gdw −1 ), and the moisture content of all the soil was adjusted to 60% of water holding capacity (WHC) using sterile deionized water.…”
Section: Soil Inoculation and Enumerationmentioning
confidence: 99%
“…Os principais sintomas clínicos causados pela infecção da E. coli enteropatogênica são a diarreia aquosa e a colite hemorrágica, que podem evoluir para a síndrome hemolítico-urêmica, pondo em risco a vida dos seres humanos e animais (SAXENA; KAUSHIK; MOHAN, 2015;INVIK et al, 2017). Esse patógeno tem transmissão fecal-oral e, uma vez no ambiente, pode se espalhar com a água da chuva, em fossas sépticas e excretas de animais expostas a céu aberto, alimentos mal higienizados e águas não tratadas (DING et al, 2018), como verificado no presente estudo. Portanto, esse microrganismo é uma ameaça ao meio ambiente e à saúde pública.…”
Section: Medeiros E Dourado (2010) Analisaram a Potabilidade Da áGua Subterrânea Daunclassified
“…A transmissão de doenças por água contaminada no meio rural é alta, pois, geralmente, esses locais são mais desassistidos quanto à atuação da Vigilância Sanitária local. Além disso, um dos principais microrganismos responsáveis por infecções gastrointestinais, facilmente transmitido pela água não tratada, é a Escherichia coli enteropatogênica, podendo ter sua origem em fossas e pastagens (DANELUZ; TESSARO, 2015; RÍOS-TOBÓN; AGUDELO-CADAVID; GUTIÉRREZ-BUILES, 2017;SCOTT;LEH;HAGGARD, 2017;DING et al, 2018). A água que abastece essas localidades frequentemente advém de poços comunitários, os quais normalmente não recebem qualquer tipo de tratamento prévio, necessitando de monitoramento dos parâmetros qualidade, conforme estabelecido no capítulo V da Portaria de Consolidação nº 5, de 28 de setembro de 2017 (BRASIL, 2017;COELHO et al, 2017).…”
unclassified